Applying the welfare model to at-own-risk discharges. (August 2017) - Krishna, Lalit Kumar Radha; Menon, Sumytra; Kanesvaran, Ravindran
"At-own-risk discharges" or "self-discharges" evidences an irretrievable breakdown in the patient–clinician relationship when patients leave care facilities before completion of medical treatment and against medical advice. Dissolution of the therapeutic relationship terminates the physician's duty of care and professional liability with respect to care of the patient. Acquiescence of an at-own-risk discharge by the clinician is seen as respecting patient autonomy. The validity of such requests pivot on the assumptions that the patient is fully informed and competent to invoke an at-own-risk discharge and that care up to the point of the at-own-risk discharge meets prevailing clinical standards. Palliative care's use of a multidisciplinary team approach challenges both these assumptions. First by establishing multiple independent therapeutic relations between professionals in the multidisciplinary team and the patient who persists despite an at-own-risk discharge. These enduring therapeutic relationships negate the suggestion that no duty of care is owed the patient. Second, the continued employ of collusion, familial determinations, and the circumnavigation of direct patient involvement in family-centric societies compromises the patient's decision-making capacity and raises questions as to the patient's decision-making capacity and their ability to assume responsibility for the repercussions of invoking an at-own-risk discharge. With the validity of at-own-risk discharge request in question and the welfare and patient interest at stake, an alternative approach to assessing at-own-risk discharge requests are called for. The welfare model circumnavigates these concerns and preserves the patient's welfare through the employ of a multidisciplinary team guided holistic appraisal of the patient's specific situation that is informed by clinical and institutional standards and evidenced-based practice. The welfare model provides a robust decision-making framework for assessing the validity of at-own-risk discharge requests on a case-by-case basis.